HOW TO DEVELOP OF PHRASAL VERBS, IDIOMS, AND COLLOCATIONS WITH THE HELP OF WEBLOGS - Badalbaeva Malokhat, Badalbaeva Malokhat (Журнал иностранных языков и лингвистики, 2021)
The development of technology including the Internet and weblogs has provided opportunities to solve the limitations of the traditional ways of teaching and learning. The present study aimed to investigate, how blogging could affect vocabulary proficiency of Uzbek students. To do the study, a group of sixty Uzbek EFL learners were selected based on their performance on oxford proficiency test (OPT). A pre-test, post-test, observation and interview were used. The results revealed that using blogs had significant role in vocabulary learning of the students. The findings of this study can be beneficial to Uzbek EFL students, teachers.